Passively mode-locked fiber laser and Q-switched fiber laser based on the graphene oxide. - Chan, Weiwei. (2013)
The fiber laser is one of the promising laser types in both research and industry. The FYP project is designed to research on the optical properties of the graphene oxide saturable absorber (GO SA) in the fiber laser. We conducted the operation on the polarization controller and the input power to achieve single-wavelength mode-locking, dual-wavelength mode-locking and the Q-switching for the Yb-doped fiber laser with the graphene oxide saturable absorber. Mathematical simulation is also used to help explain the experimental results. In the experiment, the desirable laser pulse was obtained by using the GO SA. This result supports the possibility for the future application of the GO SA. However, there is some limitation of the experiment due to the restriction of the equipment. Further work is required to support the results more strongly.